Magnesite growth inhibition by organic ligands: An experimental study at 100, 120 and 146 °C. (15th May 2016) - Gautier, Quentin; Bénézeth, Pascale; Schott, Jacques
Abstract: It has been proposed that simple organic ligands, which accelerate Mg-silicates dissolution, could be used to accelerate CO2 mineral sequestration through mineral carbonation. The influence of these ligands on magnesite growth has however never been quantified. In this work, we investigated the influence of three organic ligands: oxalate, citrate and EDTA on magnesite growth in alkaline conditions and at hydrothermal temperatures (100, 120 and 146 °C) using mixed flow reactors. We show that the studied carboxylates decrease magnesite growth rates, due to two converging mechanisms: – Complexation of Mg 2+ in solution, which decreases the saturation state of the solution. This effect was carefully taken into account by using a thermodynamic database relevant for the studied system. EDTA being the stronger chelate of the three investigated ligands, it has the strongest influence on solution saturation state. – Adsorption of the ligand on magnesite surface growth sites, which decreases the kinetic rate constant of magnesite growth. We observed the following inhibition effectiveness of investigated organic ligands: citrate > EDTA > oxalate. While citrate exerts the strongest growth inhibition due to adsorption, it does not apparently lead to a complete interruption of magnesite growth. Preliminary adsorption experiments suggest that citrate adsorbs to active growth sites at the mineral surface with a much higher affinity than for the bulk of the surface. Using experimentally retrieved magnesite growth rate laws and published forsterite (Mg2 SiO4 ) dissolution rate law, we performed simple numerical simulations to estimate the overall influence of the investigated ligands on the carbonation rates of forsterite. We observe that all ligands will clearly be detrimental to forsterite carbonation rates in typical conditions foreseen for Mg-silicates mineral carbonation. Their use may be positive for the carbonation of less reactive Mg-silicate minerals, but the delayed formation of magnesite could as well trigger the formation of secondary Mg-bearing phases which would reduce the maximal carbonation extent.